G535 PaedSCRIPT: an innovative eLearning prescribing programme for paediatric trainees. (27th April 2016) - Lissauer, S; Hay, E; Evans, E; Isaac, R; Reynolds, F; Ahmed, A; Pontefract, S; Vallance, H; Coleman, J; Goodyear, H
Abstract : Context: We describe the development of an e-learning programme for ST1-ST8 paediatric trainees. This was innovated and developed by two trainees and funded by the local deanery. The e-learning platform was developed in conjunction with the local University and Childrens Hospital. The programme is also hosted on MedsIQ and is likely to be used by other deaneries in due course. Problem: Children are at particular risk of medications errors, and the RCPCH has identified that there is need for improved prescribing in response to gross medication errors affecting children. In-patient paediatric prescribing errors occur in around 13% of prescriptions. Despite this, trainees or non-medical prescribers have no specific training in prescribing for children, or opportunity for continuing professional development. Assessment of problem and analysis of its causes: We asked local trainees (ST1-ST8) via questionnaire about competence in prescribing and the frequency of error. 90% of trainees had made a prescribing error and 30% had an incident report generated about an error. 80% felt that an e-learning tool to improve prescribing would be helpful. Deficiencies in prescribing competence and knowledge amongst senior trainees has been identified in those undertaking START. Intervention: We have developed 25 e-learning modules focused on practical safe prescribing for children. We put together an editorial board led by trainees and comprising of pharmacists, nurse prescribers and consultants. We produced a list of modules by trainee focus group and based on the curriculum. Local authors were identified for each module and were usually a trainee and pharmacist with senior support. We utilised an e-learning platform already developed for a foundation-year prescribing programme (SCRIPT). The modules take around 1 h to complete and are practical, using cases and audiovisual material and interactive in-module assessments (see Figure 1 for examples from modules). There are pre and post-test questionnaire to assess in-module progress. Focus groups of trainees were used to design length of modules and the e-learning interface. The modules are outlined in Table 1 . Strategy for change: There are currently 6 modules 'live' and all 25 modules will be launched by March 2016. These will initially be available to all paediatric trainees in the region and hosted on MedsIQ. ST1-ST8 local trainees will be required to complete all modules by the time of START assessment. Modules will also be available to other deaneries by request. Measurement of improvement and effect of change: We can use data generated by the modules to assess individual improvement throughout the modules. User feedback can be sent back and modules will be continually improved/updated. We will also assess confidence and competence by self-reported error and national incident reporting levels amongst trainees undertaking paediatric SCRIPT. We will also look at prescribing outcome from the START assessment and level of prescribing error in trainees in each trust. SCRIPT for foundation doctors has led to significant improvement in confidence around prescribing; 75% found it had positively impacted upon prescribing knowledge and skill, and 73% had changed aspects of practice. It also won a National Patient Safety award in 2013. Message: Children are at significant risk from prescribing errors. Despite this there is little specific practical prescribing training available. We have developed an innovative interactive e-learning programme in prescribing skills for trainees and non-medical prescribers. This e-learning package is unique and designed to target the needs of trainees from ST1 through to ST8 and can be used as a reference tool. The aim is to increase competence in prescribing and reduce error thus reducing patient harm.